Bahasa Inggris - Mahardiyanto*, Agus; Subagio, N. Ari; Nutqi, Crisma Winda Aniva; Prijanto, Fajar Wahyu (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
This study aims to determine the effect of brand image, electronic word of mouth, and perceived ease of use on young investors decisions in choosing Islamic mutual fund investment applications for students in Jember. This type of research uses explanatory research and uses a quantitative approach. Researchers used primary data obtained from distributing questionnaires to students in Jember with a sample of 150 respondents. The technique used was purposive sampling technique to select samples. Multiple linear regression analysis is the method used in this study using SPSS software version 26. This study shows the results that the t test (partial) variable electronic reviews and perceived convenience affect young investors in choosing an Islamic mutual fund investment application while brand image does not affect young investors decisions in choosing investment applications